Review of Completeness of General Road Care Form in The Poli MTBS UPT Puskesmas Ngoresan in 2019 - Ellen Nur Fauziah; Liss Dyah Dewi Arini; Liliek Prasetijaningsih; Ani Nur Fauziah (Proceeding of International Conference on Science, Health, And Technology, 2021)
Puskesmas Ngoresan Surakarta has a number of outpatient forms for poly MTBS until 2019, namely 3,590 forms. The large number of forms raises several problems, such as incompleteness of filling in forms based on quantitative analysis where health workers who fill out the forms are not careful about the items. The purpose of this study was to determine the completeness of outpatient forms for the MTBS poly at Puskesmas Ngoresan Surakarta in 2019. This type of research is descriptive with research methods using observation, and interviews. Cross sectional research approach. Population of 3,590 forms with a sample of 97 outpatient forms of poly MTBS. The results of the data analysis show that the review of the completeness of the outpatient poly MTBS form on the identification review is 100% complete, the reporting review is 0% complete, the authentication review is 100% complete, the recording review is 0% complete. %. Factors that affect completeness include the doctor's discipline in filling in the DRM, the doctor's accuracy in paying attention to the items that should be filled in. The conclusion of the review Identification, Reporting, Authentication, and Recording states 2 reviews, namely identification and authentication 100% complete, and 2 reviews, namely recording and reporting 0% complete. Suggestions given to the results of this study are that the Surakarta Ngoresan Health Center should improve its performance so that the completeness of the four reviews can be optimal.